Implementation of the Problem Posing Method in Increasing Student Learning Activities in Islamic Religious Education Class VIII at SMPIT Titian Ilmu Bekasi - Najiha, Izzatun; Fitrah, Ahmad Muidal; Sandy, Sandy; Ismilah, Siti (ISLAMIKA, 2024)
Education is part of future investment, community investment as well as state investment to advance and educate the nation's life. The purpose of this study is to evaluate the effectiveness of the problem posing learning method in improving student learning activities in Islamic Religious Education (PAI) class VIII at SMPIT Titian Ilmu Bekasi. This study also aims to understand the influence of this learning method on students' involvement in class discussions, enthusiasm in completing assignments, and active participation in learning. This research was conducted through analytical techniques from the data that had been obtained during research activities and the researchers attempted to explain and explain rationally, objectively with the objectives and existing research problems. The method that the researcher uses in this research is a qualitative approach with the type of naturalistic phenomenological research, namely the type of research carried out by researchers to identify human experience about a certain phenomenon naturally. Research conducted from April 12 to May 20, 2024, at SMPIT Titian Ilmu Bekasi shows that the conventional learning method of PAI is less effective in attracting student interest and involvement, so innovations such as problem posing methods are needed which are proven to increase student learning activities. PAI has an important role in shaping students' character and morals by instilling values such as honesty, responsibility, and tolerance, but it must be more relevant to students' daily lives and integrated with religion-based extracurricular activities. In conclusion, to increase the effectiveness of PAI, it is necessary to have interactive, contextual, and integrated learning with relevant practical activities, so that it can answer the challenges of the times and help students develop strong moral values.